DIGITALIZATION AND BANANA CHIP INNOVATION: EFFORTS TO INCREASE THE COMPETITIVENESS OF LOCAL UMKM IN TERATAK VILLAGE - Astiko, Wahyu; Yarti, Suci; Idyawati, Idyawati; Azhari, Baiq Septia Vina; Wati, Karisma; Tanadi, Stephannie Nandhika; Nu’aimah, Siti Orpala; Juhanda, Rizki Aprilla; Haqqi, Ahmad Dia’ul; Ramadhan, Imam Muzhaffar; Ramdhani, Abi Irfan (Jurnal Wicara, 2025)
Teratak Village, located in Batukliang Utara District, Central Lombok Regency, holds great potential for agricultural product processing, particularly bananas. The abundance of raw materials presents an opportunity to develop multi-flavored banana chips as a flagship product. Community empowerment efforts focus on flavor innovation, packaging, and digital marketing to enhance product competitiveness. Innovations include developing flavors such as chocolate, doger, and taro. Additionally, packaging plays a crucial role in increasing product value, with training provided on creating attractive, functional, and eco-friendly packaging. Informative label designs and customized packaging sizes are expected to expand market reach, including entry into supermarkets and souvenir shops. In the digital era, online marketing serves as a key strategy. The community is trained to utilize social media platforms like Instagram and Facebook, along with digital marketing strategies, to boost product visibility. Through digital marketing, Teratak Village's banana chips have the potential to gain wider recognition both nationally and internationally. This program aims to enhance community skills and creativity, create new job opportunities, and strengthen Teratak Village's identity as a center for high-quality banana chip production. This integrated approach is expected to support sustainable economic development and provide long-term benefits to the community.